Association Between Heavy Metal Exposure and Central Nervous System Tumors: A Case-Control Study Using Single and Multi-Metal Models - Sen Luo; Haixia Wu; Fang Xiao; Tianwen Yang; Wei Wang; Hang Du; Peng Su (Toxics, 2025)
(1) Background: Neoplasms of the central nervous system (CNS) encompass a cluster of malignant diseases originating from tissues or structures within the CNS. Environmental factors, including heavy metals, may contribute to their development. Therefore, this research was to investigate the association between heavy metal exposure and CNS tumor susceptibility using single and muti-metal models. (2) Methods: 63 CNS tumor patients and 71 controls were included. Urine samples from the CNS tumor patients and controls were analyzed for 47 metals using inductively coupled plasma-mass spectrometry in this study. Statistical analyses included conditional Wilcoxon rank-sum tests, logistic regression, Least Absolute Shrinkage and Selection Operator (LASSO) regression, and Bayesian Kernel Machine Regression (BKMR). (3) Results: In the single metal model, higher levels of seventeen metals might be associated with a lower incidence of CNS tumor, while higher exposure levels of five metals are associated with a higher incidence of tumor. LASSO regression selected nine metals for further BKMR analysis. The joint effects showed decreased tumor risk with increased metal mixture concentration. The level of the metals Ge, As, Rb, Zr, and Sn may be related to the incidence of meningiomas and gliomas. (4) Conclusions: This study explored the association between various metals and CNS tumors, providing ideas for future prospective cohort studies and laboratory studies, and providing a foundation for new ideas in the prevention and treatment of CNS tumors.